Superinfection in malaria: Plasmodium shows its iron will. - Portugal, S; Drakesmith, H; Mota, M (2011)
After the bite of a malaria-infected mosquito, the Plasmodium sporozoite infects liver cells and produces thousands of merozoites, which then infect red blood cells, causing malaria. In malaria-endemic areas, several hundred infected mosquitoes can bite an individual each year, increasing the risk of superinfection. However, in infants that are yet to acquire immunity, superinfections are infrequent. We have recently shown that blood-stage parasitaemia, above a minimum threshold, impairs the growth of a subsequent sporozoite infection of liver cells. Blood-stage parasites stimulate the production of the host iron-regulatory factor hepcidin, which redistributes iron away from hepatocytes, reducing the development of the iron-dependent liver stage. This could explain why Plasmodium superinfection is not often found in young nonimmune children. Here, we discuss the impact that such protection from superinfection might have in epidemiological settings or in programmes for controlling malaria, as well as how the induction of hepcidin and redistribution of iron might influence anaemia and the outcome of non-Plasmodium co-infections.